A Noble and Economical Method for the Synthesis of Low Cost Zeolites From Coal Fly Ash Waste. (30th September 2022) - Yadav, Virendra Kumar; Suriyaprabha, R; Inwati, Gajendra Kumar; Gupta, Nitin; Singh, Bijendra; Lal, Chagan; Kumar, Pankaj; Godha, Meena; Kalasariya, Haresh
ABSTRACT: Coal fly ash (CFA) is one of the major global pollutants, which is continuously invading a huge amount of land every year; consequently, there is depletion of barren land. Even, in the 21st century, a hundred per cent utilisation of fly ash is not achieved. Here, in the present research work, fly ash is processed initially with the mineral acids followed by the alkali treatment under optimised conditions. The alkali treatment of fly ash revealed the formation of geopolymers like the structure of variable shapes and sizes. The confirmation and identification of the final desilicated product were done by infrared spectroscopy i.e. (FT-IR), X-ray diffraction (XRD), X-Ray fluorescence (XRF), Field Emission Scanning Electron Microscopy (FESEM-EDS) and Transmission Electron Microscopy (TEM). The size of the zeolitic product was varying from 60 to 120 nm in width and 80 to 700 nm in length. While the shape of the particles was varying from spherical to needle and rod-shaped. The current method suggested the transformation of fly ash waste into the zeolite product. The synthesis of such particles from fly ash makes the process and product economical and eco-friendly by providing a safe and environment-friendly disposal of fly ash.